PENERAPAN TEPID WATER SPONGE UNTUK MENURUNKAN DEMAM PADA ANAK USIA TODDLER 1-3 TAHUN DENGAN KEJANG DEMAM DI RUANG KEMUNING RSUD BAYU ASIH PURWAKARTA - Wirdan Fauzi Rahman; Serly Serly; Reyda Azzahra (Jurnal Cakrawala Ilmiah, 2022)
Febrile convulsions or febrile convulsions are seizures that occur with an increase in body temperature (rectal temperature above 38˚C) which is most often found in children aged 6 months to 4 years. The World Health Organization (WHO) estimates that by 2020 the prevalence of febrile seizure patients will be more than 18.5 million and more than 155,000 of them will die. The incidence of febrile seizures in Indonesia by 2021 reaches 22.2%. Approximately 25-50% of children with febrile seizures have recurrent febrile seizures. Patients with febrile seizures need to be given compress therapy, one of which is by using the Tepid Water Sponge technique. The Tepid Water Sponge is a form of warm compress that uses the wiping technique to reduce the body temperature of patients with high fever. The purpose of this study was to describe the application of Tepid Water Sponge on An. R who had a high fever with febrile seizures. This type of research is descriptive with a case study approach method. The subjects in this study were one toddler patient aged 1-3 years with febrile seizures who experienced hyperthermia in the Kemuning room at Bayu Asih Hospital, Purwakarta. The results of this study showed that the child's temperature before being given a tepid water sponge was 38.8°C and after being given a tepid water sponge for 3 days, namely 36.5°C. The tepid water sponge nursing intervention was carried out in the morning and afternoon in a span of 15-20 minutes. The conclusion from the results of this study is that the average temperature decrease is 1°C and it can be concluded that the tepid water sponge can reduce body temperature in hyperthermic children with febrile seizures